1984
DOI: 10.1093/jnci/72.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Tumorigenicity of Human Malignant Melanocytes in Relation to Their Culture Conditions23

Abstract: The effects of variations in the concentrations of L-cystine (Cys), L-methionine (Met), and L-glutamine (Glu) on the establishment of melanocyte cell lines obtained from a primary tumor and its metastasis in the same patient were studied. The special role of Glu was also studied in 4 lymph node metastases from other patients. Differentiation in vitro was dependent on the culture conditions, as assessed by morphologic and biochemical studies. Karyologic expression, doubling time, cloning efficiency, and tumorig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Although these results contrast what might be expected based on our in vitro findings, similar findings have been observed by others [4] with human malignant melanoma grown in nude mice. Although these results contrast what might be expected based on our in vitro findings, similar findings have been observed by others [4] with human malignant melanoma grown in nude mice.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although these results contrast what might be expected based on our in vitro findings, similar findings have been observed by others [4] with human malignant melanoma grown in nude mice. Although these results contrast what might be expected based on our in vitro findings, similar findings have been observed by others [4] with human malignant melanoma grown in nude mice.…”
Section: Discussionsupporting
confidence: 71%
“…It is clear that a number of in vitro growth conditions can influence the growth and differentiation of tumor cells [4,5,19,24,28,29,35]. Any similarity in mechanisms affecting differentiation in previous reports and those observed in our system are at present unknown.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In this report we describe 5 different, original, permanent cell lines obtained from the 3 kinds of ocular melanoma. Our rcsults indicate substantial differences in the behavior of malignant nielanocytes obtained from 3 primary uveal tumors, in particular when these are compared to our 18 established cell lines derived from primary cutaneous melanomas (Aubert et al, 1980b(Aubert et al, , 1984 and the 3 new ones reported here. The biological characteristics of conjunctival melanomas do not differ significantly from those of cutaneous melanomas (Bernardino et al, 1976).…”
Section: Discussionmentioning
confidence: 56%
“…Melanomas are favorite models for such studies, as their cells contain easily recognized markers of differentiation, such as melanin, tyrosinase, or the formation of cell processes. They were found to differentiate spontaneously in vitro [139][140][141] or under the influence of MSH [142][143][144], cAMP [145], theophylline [143,146,147], colcemid and arabinofurasonylcytosine [148], anthracycline antibiotics [149], dimethyl sulfoxide and phorbol esters [150][151][152], retinoids [153], guanosine triphosphate [154], tritiated thymidine [155], and polyamine antimetabolites [156]. Among the instances of melanoma cell differentiation in vitro, the case of the Ab melanoma is most peculiar because the cells, which are completely amelanotic in vivo, melanize heavily during a few days in a standard in vitro condition, without any additional treatment.…”
Section: Melanization Of Amelanotic Variant In Vitromentioning
confidence: 99%